(untitled) (Eurasian Journal of Ecology, 2026)
Bacterial cellulose (BC) is considered a promising biopolymer for the development of biodegradable packaging materials due to its high purity, nanofibrillar structure, biocompatibility, and potential for functional modification. The aim of this review is to analyze current studies focused on BC production, its physicomechanical and barrier properties, functionalization methods, as well as its application in active and intelligent food packaging. A literature search was conducted in the Scopus, Web of Science, and Google Scholar databases for the period 2009–2024 using the keywords “bacterial cellulose,” “food packaging,” “active packaging,” “smart packaging,” and “biocomposites.” More than 120 publications were analyzed, of which 95 of the most relevant sources were selected. It has been shown that the main limitations of native BC remain its high hydrophilicity, insufficient stability in humid environments, and lack of intrinsic antimicrobial activity. These drawbacks can be effectively overcome through in situ and ex situ modifications using biopolymers, nanoparticles, and bioactive compounds. Particular attention is given to BC-based active and intelligent systems that provide antimicrobial protection, antioxidant release, and monitoring of food freshness. At the same time, unresolved issues related to scale-up, migration of functional additives, and economic feasibility are highlighted. It is concluded that further commercialization of BC-based packaging requires comprehensive optimization of biosynthesis processes, composite properties, and life cycle assessment. Key words: bacterial cellulose, biopackaging, food packaging, biopolymer, biocomposite.